Maldives : Use of Fund Resources-Request for Emergency Assistance. (IMF Staff Country Reports; Country Report ;, 2005)
This paper reviews the Maldives's Use of IMF Resources and Request for Emergency Assistance. The authorities have requested a purchase of an amount equivalent to SDR 4.1 million (50 percent of quota) under the IMF's policy on emergency assistance related to natural disasters. The authorities have requested the provision of subsidies to reduce the rate of charge on these resources. IMF staff supports these requests given the exceptional severity of the tsunami's economic impact and the authorities' record of sound macroeconomic management and good cooperation with the IMF.